Current medical diagnosis & treatment - 4 0 16; 1919- Tierney, Lawrence,;McPhee, Stephen J.;Papadakis, Maxine A.; 5 (Stamford, CT : Appleton & Lange, 1997)
A comprehensive reference source for questions arising in the clinical practice of medicine. Includes information pertaining to all medical fields as well as advice on outpatient and inpatient management.
A Lange medical book.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Diagnosis;Diseases;Therapeutics;Diagnosis;Diseases;Therapeutics -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2